Description of the final instar larva of Limnetron antarcticum Förster and notes on its female (Anisoptera: Aeshnidae) - del Palacio, Alejandro (2014)
The final instar larva of Limnetron antarcticum Förster is described and illustrated for the first time based on one specimen collected in Misiones Province, Argentina. It is compared with L. debile (Karsch). Color pattern and ovipositor morphology of the female imago are described.